Electronic band structure of optimal superconductors: from cuprates to ferropnictides and back again (Review Article) - Kordyuk, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
While the beginning decade of the high-Tc cuprates era passed under domination of local theories, Abrikosov was one of the few who took seriously the electronic band structure of cuprates, stressing the importance of an extended Van Hove singularity near the Fermi level. These ideas have not been widely accepted that time mainly because of a lack of experimental evidence for correlation between saddle point position and superconductivity. In this short contribution, based on the detailed comparison of the electronic band structures of different families of cuprates and iron-based superconductors I argue that a general mechanism of the Tc enhancement in all known high-Tc superconductors is likely related with the proximity of certain Van Hove singularities to the Fermi level. While this mechanism remains to be fully understood, one may conclude that it is not related with the electron density of states but likely with some kind of resonances caused by a proximity of the Fermi surface to topological Lifshitz transition. One may also notice that the electronic correlations often shift the electronic bands to optimal for superconductivity positions.